2016
DOI: 10.2118/174192-pa
|View full text |Cite
|
Sign up to set email alerts
|

Analytical Evaluation of Nanoparticle Application To Mitigate Fines Migration in Porous Media

Abstract: This paper examines an application of the method of characteristics (MOC) to evaluate the effectiveness of nanoparticles to mitigate fines migration in porous media. The positive contribution of nanoparticles to mitigate fines migration was characterized by the increase of maximum retention concentration of fines particles on rock grains through two reactions described in this paper: (1) adsorption of nanoparticles onto the fines/grain surface and (2) increased retention of fines attachment on the pore surface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(19 citation statements)
references
References 42 publications
(50 reference statements)
0
19
0
Order By: Relevance
“…This function is called the maximum retention function σ cr (U,γ,pH,T) and models particle detachment: if the initial concentration of attached fines is σ aI , applying the flow with velocity U, salinity γ, pH, and temperature T results in release and mobilization of σ aIσ cr (U,γ,pH,T) fine particles. The maximum retention function closes the governing system for a singlephase and a two-phase suspension-colloidal-nano transport equations (Yuan et al, 2016;Yuan & Moghanloo, 2017;Yuan & Shapiro, 2011).…”
Section: Figures S4 and S5mentioning
confidence: 56%
“…This function is called the maximum retention function σ cr (U,γ,pH,T) and models particle detachment: if the initial concentration of attached fines is σ aI , applying the flow with velocity U, salinity γ, pH, and temperature T results in release and mobilization of σ aIσ cr (U,γ,pH,T) fine particles. The maximum retention function closes the governing system for a singlephase and a two-phase suspension-colloidal-nano transport equations (Yuan et al, 2016;Yuan & Moghanloo, 2017;Yuan & Shapiro, 2011).…”
Section: Figures S4 and S5mentioning
confidence: 56%
“…Particle transport behavior is the issue that petroleum engineers attempted to solve for many years because particulate flow systems exist in a wide range of petroleum related processes, for example the injection of seawater during water flooding, invasion of filtrate during drilling, and micro enhanced oil recovery (Yuan et al 2016). The formation damage caused by fine particle retention and detachment highly effect the productivity and injectivity of wells (Bedrikovetsky et al 2011).…”
Section: Scope Of the Problemmentioning
confidence: 99%
“…Nanoparticles have showed remarkable performance in fixing the formation fines during fracturing activities [12]. Several studies suggested the nanoparticles has the effect of strengthening the attractive forces with regards to the repulsive forces and prevent the detachment of fines particles from the pore walls [15].…”
Section: Introductionmentioning
confidence: 99%